2010
DOI: 10.1007/s11664-010-1138-z
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Defect Production Rates in n-Type Silicon by Hydrogen Implantation Near 270 K

Abstract: Defect production behavior in hydrogen-implanted n-type silicon has been studied by varying the implantation temperature from 88 K to 303 K. Deep-level transient spectroscopy has been used to reveal electron trap spectra for Schottky diodes fabricated at room temperature after implantation. Metastable defects are observed in addition to vacancy-and hydrogen-related defects. It is found that the production rates of these defects are greatly enhanced by hydrogen implantation near 270 K. It is suggested that hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Hydrogenation of TFT by ion implantation is not a frequently used process [19] and there is no evidence of its impact on poly-Si defect generation. However, for single crystal silicon it was demonstrated that hydrogen implantation causes creation of different defects [20], which may explain more abundant grain boundary trap generation for our studied hydrogenated devices at higher radiation gamma-ray doses.…”
Section: Grain Boundaries Trap Analysismentioning
confidence: 80%
“…Hydrogenation of TFT by ion implantation is not a frequently used process [19] and there is no evidence of its impact on poly-Si defect generation. However, for single crystal silicon it was demonstrated that hydrogen implantation causes creation of different defects [20], which may explain more abundant grain boundary trap generation for our studied hydrogenated devices at higher radiation gamma-ray doses.…”
Section: Grain Boundaries Trap Analysismentioning
confidence: 80%